Comparative Effectiveness of Ceftriaxone Alone and in Combination with Clarithromycin for Paediatric Patients Hospitalized with Community Acquired Pneumonia - Lubna Riaz, Mohamed Fayez Gebril, Tayyaba Rasheed, Maria Javed, Muhammad Naveed, Zainab Riaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Guidelines for treatment of community acquired pneumonia suggests empirical therapy with combination of clarithromycin and ceftriaxone when infection with mycoplasma pneumoniae is considered. But there is limited evidence available. Aim: To ascertain effectiveness of ceftriaxone alone verses the combination of ceftriaxone and clarithromycin with respect to cure and length-of-stay and total hospital cost. Methodology: A randomized control trial with 128 patients of age 2 months to 5 years was conducted at Department of Paediatrics, Shaikh Zayed Hospital Lahore from 1st October 2017 to 30th September 2018. Patients selected according to selection criteria through non probability sampling technique and randomly divided into two groups. Antibiotics given according to study objectives, comparative analysis done, and chi square test applied. Results: The mean age of patients were 27.02±19.28 months in group A and 29.06±18.29 months in group B. In both groups most of the patients were under the age of 40 months. 72% cured in group A while 86% cured in group B. 80% patients stayed in hospital for 3 days in Group A while, 59% patients in group B. 69% patients had cost effectivity in group A while 84% in group B. Conclusion: The combination of Ceftriaxone and Clarithromycin was more advisable in treating pnemounia verses the use of ceftriaxone alone. Keywords: Community acquired pneumonia, Ceftriaxone alone, Ceftriaxone and clarithromycin, Mycoplasma pneumonia